Novel antibodies against GPIbα inhibit pulmonary metastasis by affecting vWF-GPIbα interaction - Yingxue Qi; Wenchun Chen; Xinyu Liang; Ke Xu; Xiangyu Gu; Fengying Wu; Xuemei Fan; Shengxiang Ren; Junling Liu; Jun Zhang; Renhao Li; Jianwen Liu; et al. (Journal of Hematology & Oncology, 2018)
Abstract Background Platelet glycoprotein Ibα (GPIbα) extracellular domain, which is part of the receptor complex GPIb-IX-V, plays an important role in tumor metastasis. However, the mechanism through which GPIbα participates in the metastatic process remains unclear. In addition, potential bleeding complication remains an obstacle for the clinical use of anti-platelet agents in cancer therapy. Methods We established a series of screening models and obtained rat anti-mouse GPIbα monoclonal antibodies (mAb) 1D12 and 2B4 that demonstrated potential value in suppressing cancer metastasis. To validate our findings, we further obtained mouse anti-human GPIbα monoclonal antibody YQ3 through the same approach. Results 1D12 and 2B4 affected the von Willebrand factor (vWF)-GPIbα interaction via binding to GPIbα aa 41-50 and aa 277-290 respectively, which markedly inhibited the interaction among platelets, tumor cells, and endothelial cells in vitro, and reduced the mean number of surface nodules in the experimental and spontaneous metastasis models in vivo. As expected, YQ3 inhibited lung cancer adhesion and demonstrated similar value in metastasis. More importantly, for all three mAbs in our study, none of their Fabs induced thrombocytopenia. Conclusion Our results therefore supported the hypothesis that GPIbα contributes to tumor metastasis and suggested potential value of using anti-GPIbα mAb to suppress cancer metastasis.